2022
DOI: 10.1097/qai.0000000000002915
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Transgender Women and Preexposure Prophylaxis Care: High Preexposure Prophylaxis Adherence in a Real-World Health Care Setting in New York City

Abstract: Background: Transgender women and trans feminine individuals (TGW/TFI) are a high priority population for the provision of HIV preexposure prophylaxis (PrEP) care within the United States, but there is limited research that focuses specifically on PrEP adherence within this population.Setting: Observational study of patients prescribed PrEP at a community-based health center. Methods:We enrolled 100 TGW/TFI PrEP patients at a community health center during clinic visits. Adherence data were collected at 3 time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
(61 reference statements)
1
2
0
Order By: Relevance
“…Other studies conducted among those on antiretroviral treatment in South Africa [ 19 ] and female PrEP users in Kenya [ 18 ] confirmed the acceptability of the urine test. Our research findings align with these studies and a similar one involving 100 TGW and men prescribed PrEP in the United States, which reported a strong correlation between self‐reported adherence to PrEP and the detection of tenofovir in urine samples [ 34 ]. Our finding of initially negative emotions and distrust in POC urine testing underscores the importance of tailored adherence counselling.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies conducted among those on antiretroviral treatment in South Africa [ 19 ] and female PrEP users in Kenya [ 18 ] confirmed the acceptability of the urine test. Our research findings align with these studies and a similar one involving 100 TGW and men prescribed PrEP in the United States, which reported a strong correlation between self‐reported adherence to PrEP and the detection of tenofovir in urine samples [ 34 ]. Our finding of initially negative emotions and distrust in POC urine testing underscores the importance of tailored adherence counselling.…”
Section: Discussionsupporting
confidence: 90%
“…Limited findings herein suggest that among those taking PrEP very recently (last month), adherence was high. Similarly in a prior study among trans women taking PrEP, there was evidence of high adherence, but also intermittent stoppage over time [ 19 ].…”
Section: Discussionmentioning
confidence: 67%
“…At the clinic-level, a select few US- and international-based demonstration projects have shown some promising successes in implementing the integration of gender-affirming care with PrEP services, with the majority primarily designed to increase PrEP uptake among transfeminine adults in community-based health clinic settings. For example, researchers at Callen Lorde Community Health Center in New York City, an LGBTQ-focused health center that specializes in the integration of PrEP, gender-affirming care, as well as insurance and payment services, recently published a longitudinal study that showed PrEP adherence was high (greater than 90%) at 3 and 6 months after initiation both in self-report and urine assay data collection among 80% of the 100 enrolled transfeminine patients [ 51 ]. In Atlanta, a patient-centered PrEP program designed with a co-located gender clinic offering affordable comprehensive primary care, gender-affirming hormone, and mental health services showed high rates of linkage to PrEP care, prescription, and initiation among transfeminine participants.…”
Section: Persistence For Gender-affirmative Prep Systems and Trans En...mentioning
confidence: 99%